Perception of canine rabies among pupils under 15 years in Kwara State, North Central Nigeria. - Ahmad Ibrahim Al-Mustapha; Folashade O Bamidele; Ahmed Tijani Abubakar; Ahmed Ibrahim; Muftau Oyewo; Ibrahim Abdulrahim; Jimoh Muhammad Yakub; Idris A Olanrewaju; Nusirat Elelu; Andy Gibson; Stella Mazeri; Muhammad Bashir Bolajoko (Public Library of Science (PLoS), 2022)
Rabies is an endemic, highly fatal, and vaccine-preventable disease with severe socio-economic implications. Most (99%) human rabies cases are transmitted through dog bites. Children under 15 years account for 40% of all dog bite victims and 35-50% of all rabies deaths. Rabies awareness among this vulnerable group is critical to rabies prevention. However, there is a paucity of data on rabies awareness among pupils under 15. Hence, this study assessed the awareness and attitude of pupils under 15 years towards canine rabies in Kwara state in Nigeria. The study was conducted as a cross-sectional survey of 1,388 pupils across the state using a structured questionnaire that was administered as a one-on-one interview using the Open Data Kit on Android phones in December 2019. Of the 1388 pupils included in this study, only 21.7% (n = 301) of them were aware of rabies. The mean rabies score was 1.7±0.8 and only 29.2% (n = 88/301) of the pupils had adequate knowledge of canine rabies. The dog ownership rate was 18.7% (n = 259) with an average of 1.93 dogs per household. Approximately 5% (n = 66) of the pupils have been previously bitten by a dog. One-third of the dog bite victims (35%, n = 23/66) were managed and treated at home and only 12% (n = 8/66) were treated in a health facility. The result of the multivariable logistic regression showed that students aged between 13-15 years were more likely (OR: 1.93; 95% CI: 0.72-3.01; p < 0.001) to have adequate knowledge of rabies than the younger pupils. Similarly, pupils that have dogs in their households (OR: 2.09; 95%CI: 1.49-2.75; p < 0.001) and those that reside in Kwara South (OR:1.78 95% CI:1.29, 2.44; p < 0.001) were more likely to be aware and have adequate knowledge of canine rabies respectively. Finally, Pupils from non-dog-owning households were more likely (OR:2.2; 95% CI: 1.45, 4.42; p < 0.001) to have been bitten by dogs than those from dog-owning households. The awareness and attitude of pupils under 15 to canine rabies was poor. We advocate the introduction of rabies lessons into the school curriculum in Kwara State to reduce the incidence of dog bites and prevent dog-mediated human rabies.